PENGARUH EKSPOR NETTO, KURS DOLLAR AS, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 1989-2019 - Pratama, Alfian Wedra; Sutrisna, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022DO - 10.24843/EEB.2022.v11.i02.p02, 2022)
Economic growth is the development of activities in the economy that causes goods and services produced by the community to increase. Economic growth in a country can be seen from the Gross Domestic Product. Economic growth in Indonesia fluctuates, it is important to study and analyze the factors that affect economic growth in Indonesia. The purpose of conducting this study was to determine the effect of the independent variables of this study, namely net exports, the US dollar exchange rate, and inflation on economic growth in Indonesia in 1989-2019. This research is a quantitative research with secondary data form. Data were collected through non-participant observation methods, and processed using multiple linear regression analysis techniques with time series data from 1989–2019. The results showed that net exports, the US dollar exchange rate, and inflation simultaneously had a significant and significant effect on economic growth in Indonesia. The results of the t test show that the net export variable has a positive effect on economic growth in Indonesia, while the US dollar exchange rate and inflation variables have a negative effect on economic growth in Indonesia.